2005
DOI: 10.1103/physrevlett.94.078102
|View full text |Cite
|
Sign up to set email alerts
|

Protein Structural Change Upon Ligand Binding: Linear Response Theory

Abstract: A simple formula based on linear response theory is proposed to explain and predict the structural change of proteins upon ligand binding. By regarding ligand binding as an external perturbation, the structural change as a response is described by atomic fluctuations in the ligand-free form and the protein-ligand interactions. The results for three protein systems of various sizes are consistent with the observations in the crystal structures, confirming the validity of the linear relationship between the equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
293
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(299 citation statements)
references
References 22 publications
6
293
0
Order By: Relevance
“…This parallelism is reminiscent of the linear-response behavior. 11,12,37 In the linear-response- type approximation, (the electrostatic contribution to) μ is estimated as u elec /2, where u elec is the electrostatic part of u . 11,12 For the present set of protein conformations, the electrostatic contribution u elec to u is in the range of −4800 to −4200 kcal/mol and the van der Waals contribution is in −200 to −180 kcal/mol.…”
mentioning
confidence: 99%
“…This parallelism is reminiscent of the linear-response behavior. 11,12,37 In the linear-response- type approximation, (the electrostatic contribution to) μ is estimated as u elec /2, where u elec is the electrostatic part of u . 11,12 For the present set of protein conformations, the electrostatic contribution u elec to u is in the range of −4800 to −4200 kcal/mol and the van der Waals contribution is in −200 to −180 kcal/mol.…”
mentioning
confidence: 99%
“…The principle of these applications is to perturb a known structure along its low-frequency modes so as to get a deformed structure that is consistent with low-resolution biophysical data, which are obtained after the protein has undergone some large amplitude conformational change. It was also shown that when variations of a few key distances are known, through spectroscopic measurements, for instance, it is possible, using linear response theory, to identify which modes are the most involved in the conformational change [18,19]. However, if such experimental data are missing, it is difficult to guess which low-frequency modes are the functional ones.…”
mentioning
confidence: 99%
“…Indeed, comparisons between movements in the low frequency modes of ENMs with functional movements derived from pairs of X-ray structures [8] suggest the same level of correspondence seen in similar studies using accurate force-field normal mode analysis. The binding of a ligand to a biomolecule gives rise to specific forces that induce the conformational change [9][10][11], and a pertinent question is whether these forces applied to a harmonic model of the biomolecule would produce a movement that corresponds well to the experimentally determined functional movement. Ikeguchi et al [10] have already performed such an analysis on harmonic models derived from MD simulations using quasi-harmonic analysis and also to an ENM.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of a ligand to a biomolecule gives rise to specific forces that induce the conformational change [9][10][11], and a pertinent question is whether these forces applied to a harmonic model of the biomolecule would produce a movement that corresponds well to the experimentally determined functional movement. Ikeguchi et al [10] have already performed such an analysis on harmonic models derived from MD simulations using quasi-harmonic analysis and also to an ENM. Their results are very encouraging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation